Indústria 4.0: análise da percepção de gestores de empresa de tecnologia sobre as competências necessárias dos seus colaboradores em meio à quarta revolução industrial - Fischer, Natália Agostinho (2024)
The main objective of the study was to analyze managers' perception of the skills seen as necessary for industry 4.0. For this, a questionnaire was applied with questions about the level of importance of skills that the manager considered important to his employees, as well as the performance in each of them. The research was applied in a technology company in Ponta Grossa - Paraná, with the participation of 17 managers from different areas. It was observed that the skill considered most important for managers refers to professional ethics, tolerance to diversity and reliability, from the domain of soft skills. Furthermore, this study contributes, in several aspects, to the search for the best way to focus on developing skills to adapt to the needs of the fourth industrial revolution.